Cost-effectiveness analysis of intra-articular injections of a high molecular weight bioengineered hyaluronic acid for the treatment of osteoarthritis knee pain. (May 2014) - Hatoum, Hind T.; Fierlinger, Anke L.; Lin, Swu-Jane; Altman, Roy D.
Abstract Objective: To determine the cost-effectiveness of bioengineered hyaluronic acid (BioHA, 1% sodium hyaluronate) intra-articular injections in treating osteoarthritis knee pain in poor responders to conventional care (CC) including non-steroidal anti-inflammatory drugs (NSAIDs) and analgesics. Methods: Two decision analytic models compared BioHA treatment with either continuation of patient's baseline CC with no assumption of disease progression (Model 1), or CC including escalating care costs due to disease progression (NSAIDs and analgesics, corticosteroid injections, and surgery; Model 2). Analyses were based on patients who received two courses of 3-weekly intra-articular BioHA (26-week FLEXX Trial + 26-week Extension Study). BioHA group costs included fees for physician assessment and injection regimen, plus half of CC costs. Cost-effectiveness ratios were expressed as averages and incremental costs per QALY. One-way sensitivity analyses used the 95% confidence interval (CI) of QALYs gained in BioHA-treated patients, and ±20% of BioHA treatment and CC costs. Probabilistic sensitivity analyses were performed for Model 2. Results: For 214 BioHA patients, the average utility gain was 0.163 QALYs (95% CI = −0.162 to 0.488) over 52 weeks. Model 1 treatment costs were 3469 and 4562 for the BioHA and CC groups, respectively; sensitivity analyses showed BioHA to be the dominant treatment strategy, except when at the lower end of the 95% CI. Model 2 annual treatment costs per QALY gained were 1446 and 516 for the BioHA and CC groups, respectively. Using CC as baseline strategy, the incremental cost-effectiveness ratio (ICER) of BioHA was 38, 741/QALY gained, and was sensitive to response rates in either the BioHA or CC groups. Conclusion: BioHA is less costly and more effective than CC with NSAIDs and analgesics, and is the dominant treatment strategy. Compared with escalating CC, the 38, 741/QALY ICER of BioHA remains within the 50, 000 per QALY willingness-to-pay threshold to adopt a new technology.